Research projects about diversity, ecology, movement, virulence and biotechnological potential of Listeria spp. isolated in Costa Rica from food, clinic and environmental samples - Núñez-Montero, Kattia (2019)
The genus Listeria is composed of more than 15 species, which can be isolated from different environments, including vegetation, soil, water and animals. L. monocytogenes has been studied worldwide as a model of intracellular pathogenesis, which has allowed deciphering important information on the behavior of the pathogen, such as the response to intracellular antibiotic activity, transcription of genes during intracellular life and development of in vivo models for the study of infections. Costa Rica is one of the most biologically rich nations in the world, being of interest for studies of genetic diversity in organisms. Therefore, most studies conducted in the country focus on the isolation of Listeria spp. to determine the presence or absence of the microorganism in samples of interest, being the foodstuffs the most analyzed. The little genetic information on these bacteria, led researchers from the Biotechnology Research Center of TEC, together with national and international collaborators, to carry out the first study on the genetic diversity of Listeria spp. in Costa Rica. Since then the research projects in Listeria spp. that have been developed at the CIB have a scientific scope that allow the understanding of the bacteria present in our environment, their pathogenic potential, traceability, contamination control and biotechnological potential. Likewise, it is intended to maintain and strengthen important national and international collaborations with a view to forming a network oriented to research applied to the sector of food infections in the country.